Long-term experimental hybridisation results in the evolution of a new sex chromosome in swordtail fish. Issue 1 (December 2018) - Franchini, Paolo; Jones, Julia; Xiong, Peiwen; Kneitz, Susanne; Gompert, Zachariah; Warren, Wesley; Walter, Ronald; Meyer, Axel; Schartl, Manfred
Abstract The remarkable diversity of sex determination mechanisms known in fish may be fuelled by exceptionally high rates of sex chromosome turnovers or transitions. However, the evolutionary causes and genomic mechanisms underlying this variation and instability are yet to be understood. Here we report on an over 30-year evolutionary experiment in which we tested the genomic consequences of hybridisation and selection between twoXiphophorus fish species with different sex chromosome systems. We find that introgression and imposing selection for pigmentation phenotypes results in the retention of an unexpectedly large maternally derived genomic region. During the hybridisation process, the sex-determining region of the X chromosome from one parental species was translocated to an autosome in the hybrids leading to the evolution of a new sex chromosome. Our results highlight the complexity of factors contributing to patterns observed in hybrid genomes, and we experimentally demonstrate that hybridisation can catalyze rapid evolution of a new sex chromosome. Fish have a high diversity of sex-determining systems, but the mechanisms responsible for this are not well understood. Here, Franchini et al. show how hybridization and backcrossing have led to the evolution of a new sex chromosome in swordtail fish during 30 years of experimental evolution.